PENGARUH CITRA DAYA TARIK WISATA TERHADAP KEPUASAN PENGUNJUNG DAN IMPLIKASINYA PADA LOYALITAS PENGUNJUNG DI TAMANSARI GUA SUNYARAGI - Naomi Kamal Gusman, - (2020)
This study aims to analyze the influence of tourist attraction imagery on visitor satisfaction and its implications on visitor loyalty in Tamansari Gua Sunyaragi. This type of research is an explanatory research with a quantitative approach using path analysis, there are three variables used, namely tourist attraction image variables, visitor satisfaction variables, and visitor loyalty variables, data obtained using a questionnaire as a research instrument to 200 respondents. The sampling technique is using accidental sampling with a population of visitors who are visiting Tamansari Gua Sunyaragi. The results of this study indicate that the level of image of tourist attraction in Tamansari Gua Sunyaragi is in the good category, the level of visitor satisfaction is in the good category, and the level of visitor loyalty is in the good category. And the image of tourist attraction directly and positively influences visitor loyalty without being mediated by visitor satisfaction. Based on the results of the study, managers should pay attention to the quality of service in order to improve a better image, managers need to take care of attraction rides regularly so that rides remain in a condition suitable for use and attractive, and managers are advised to make tour packages with the kratons in Cirebon to increase the number of visits and facilitate the promotion of tourism in Cirebon.